Aggregation-induced emission-active antibacterial hydrogel with self-indicating ability for real-time monitoring of drug release process. (August 2021) - Wang, Y.; Zhao, J.; Dong, Z.; Wang, C.; Meng, H.; Li, Y.; Jin, H.; Wang, C.
Abstract: Although antibacterial hydrogels are emerging as promising biomaterials for effective inhibition of bacterial infections, monitoring their dynamic release behaviors in a visual manner remains greatly challenging. Herein, non-conjugated luminescent polymers (NCLPs) with aggregation-induced emission (AIE) characteristics are used for the first time to develop a visualization strategy to monitor the release process of the drug-loaded hydrogel. The novel antimicrobial peptide polymers with intrinsic AIE effect, namely nanoengineered peptide-grafted hyperbranched polymers (NPGHPs), are encapsulated in an anionic polyelectrolyte to construct the AIE-active fluorescent polymeric hydrogel (NPGHPs/SA gel). Interestingly, the rigid environment mediated by hydrogen bonding and electrostatic interaction contributes to promoting the unconventional luminescence of fluorescent clusters. Moreover, the successive drug release process of NPGHPs/SA gel can be tracked in real time by using fluorescence microscopy. The hydrogel also has potent antibacterial activities against Gram-negative bacteria ( E. coli, P. aeruginosa ) and Gram-positive bacteria ( S. aureus, B. subtilis ). Overall, this work not only provides an advanced biomedical material with broad-spectrum antibacterial ability but also opens a facile avenue up for the investigation of drug release from gel systems. Graphical abstract: A novel self-indicating hydrogel with aggregation-induced emission property is constructed, which not only provides an advanced antibacterial biomedical material but also allows real-time visualization of the drug release process. Image 1 Highlights: A novel polymeric fluorescent hydrogel was prepared from NPGHPs and alginate. Aggregation-induced emission property was observed for NPGHPs/SA gel. The dynamic drug release process was monitored via the self-indicating gel system. The hydrogel showed broad-spectrum antibacterial activity and biocompatibility.